"Other" psychologists: An autoethnographic conversation about difference, deviance and defiance. (May 2022) - Harvey, Clare; Kotze, Elliott
Within the framework of the current drive to transform psychology in South Africa, this paper highlights "other" axes of identity that are arguably largely overlooked within the field. The conversation exposes the discipline of psychology – specifically within the South African context – and its many unexamined assumptions concerning "expected" identities of psychologists – specifically, those along heterosexual and able-bodied lines. By engaging in an autoethnographic conversation, the two authors, both "other", practising psychologists – one queer, one disabled – share and reflect on some of their experiences of feeling othered in their chosen profession. Drawing on parts of queer theory, critical disability literature, as well as the theoretical framework of biopolitical power, we start to make sense of our experiences of difference, deviance, and defiance. How the field of psychology marginalises "other" psychologists, and the impacts on those who bear the oppressions, is exposed; and a conversation is begun in which the discipline's assumptions around compulsory forms of identity – straight, not disabled, among others – are disrupted in productive ways.